2018
DOI: 10.3390/molecules23030591
|View full text |Cite
|
Sign up to set email alerts
|

Two New Anisic Acid Derivatives from Endophytic Fungus Rhizopycnis vagum Nitaf22 and Their Antibacterial Activity

Abstract: Rhizopycnis acids A (1) and B (2), two new anisic acid derivatives, were obtained from the ethyl acetate extract of the fermentation cultures of Rhizopycnis vagum, an endophytic fungus isolated from the healthy tissues of Nicotiana tabacum. The structures of the two compounds were determined through a series of 1D and 2D NMR and HRMS spectral analyses. Both compounds were the first anisic acid derivatives containing methylbutanoic/methylbutenoic acid group found in fungi. 1 and 2 displayed antibacterial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In this study, rhizovagine A (1), the rst fungal pyrrolidinooxazolidine alkaloid, bearing an unprecedented pentacyclic skeleton was isolated. The structure was elucidated by comprehensive spectroscopic analysis, together with quantumchemical 13 C NMR and ECD calculations. Compound 1 showed AchE-inhibitory activity, which could serve as a scaffold for developing new AchE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, rhizovagine A (1), the rst fungal pyrrolidinooxazolidine alkaloid, bearing an unprecedented pentacyclic skeleton was isolated. The structure was elucidated by comprehensive spectroscopic analysis, together with quantumchemical 13 C NMR and ECD calculations. Compound 1 showed AchE-inhibitory activity, which could serve as a scaffold for developing new AchE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution electrospray ionization mass spectrometry (HRESIMS) spectra were recorded on a LC 1260/Q-TOF-MS 6520 machine (Agilent Technologies, Santa Clara, CA). 1 H, 13 C, and 2D NMR spectra were measured on Bruker Avance 400 NMR spectrometers (Bruker BioSpin, Zürich, Switzerland). 1 H and 13 C NMR chemical shis were expressed in d (ppm) referring to the inner standard tetramethylsilane (TMS), and coupling constants in Hertz.…”
Section: General Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, plants can metabolize compounds produced by endophytes, and vice versa [ 4 ]. This complex network of chemical communication and metabolic activity between organisms produces new natural compounds with antifungal, antibacterial, and/or antitumor activities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Between 2012 and 2014, Chagas et al [ 7 ] reported more than 300 new metabolic compounds produced by endophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopycnis vagum was an endophytic fungus previously isolated from Nicotiana tabacum. This fungus was capable to produce a plethora of dibenzo-α-pyrone derivatives and two anisic acid derivatives (Lai et al, 2016;Wang et al, 2018Wang et al, , 2020. In our continuing interests in searching for new bioactive substances, we carried out a further chemical investigation of this fungus.…”
Section: Introductionmentioning
confidence: 99%